(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
In the present article the lexical, phraseological, phonetical, morphological and syntectical peculiarities of South-Eastern dialects fixed in the poetry of Ivan Manzhura at the end of the 19 th century are described.